Intraocular Bleeding in Patients With Atrial Fibrillation Treated With NOACs VS. Warfarin: A Systematic Review and Meta-Analysis - Liu, Fuwei; Zhang, Yupei; Luo, Jun; Zhou, Yue (Frontiers in Cardiovascular Medicine, 2022)
Background Intraocular bleeding is a devastating adverse event for patients with atrial fibrillation (AF) receiving anticoagulant therapy. It is unknown whether non-vitamin K oral anticoagulants (NOACs) compared with warfarin can reduce the risk of intraocular bleeding in patients with AF. Herein, we conducted a meta-analysis to evaluate the effect of NOACs versus warfarin on intraocular bleeding in the AF population. Methods Studies were systematically searched from the Embase, PubMed, and Cochrane databases until April 2022. We included studies if they enrolled patients with AF and compared the intraocular bleeding risk between NOACs and warfarin and if they were randomized controlled trials (RCTs) or observational cohort studies. The random-effects model was chosen to evaluate the pooled odds ratios (ORs) and 95% confidence intervals (CIs). Results A total of 193,980 patients with AF from 5 randomized controlled trials (RCTs) and 1 cohort study were included. The incidence of intraocular bleeding among AF patients treated with warfarin and NOACs was 0.87% (n=501/57346) and 0.61% (n=836/136634), respectively. In the pooled analysis with the random-effects model, the use of NOACs was not significantly associated with the risk of intraocular bleeding (OR=0.74; 95% CI 0.52-1.04, P=0.08) compared with warfarin use. In addition, the sensitivity analysis with the fixed-effects model suggested that NOAC users had a lower incidence of intraocular bleeding than patients with warfarin (OR=0.57; 95% CI 0.51-0.63, P<0.00001). Conclusions Our current meta-analysis suggested that the use of NOACs had no increase in the incidence of intraocular bleeding compared with warfarin use in patients with AF. Whether the use of NOACs is superior to warfarin needs more research to confirm.